Spoken Fluency Practices in Increasing Language Learners Performance - Magdalena Kartikasari Tandy Rerung (Universitas Bunda Mulia, 2017)
In order to communicate effectively, language skills and knowledge should be integrated and reach the goal of communication. Language knowledge is taught meanwhile skills are developed, both takes time but the skills consume longer. Fluency in this case holds an important role especially in productive skills. As EFL (English as a Foreign Language) learners who just enrolled in the English program, having a low fluency mostly occurred. Regarding to that these learners are probably passive language users therefore there are some trainings to increase their productive as well receptive skills. This study focuses on spoken fluency with the goal to reach a comprehensive utterances and ideas once their scores increased. By applying 4/3/2 fluency techniques hopefully students speaking performance would be well-developed. The experimental research will take place in UBM and the subjects are 7 students of English Language and Culture Department. The procedure will apply a recording application and analyze with a mixed-method (quantitative and qualitative). Keywords: spoken fluency, language learning, EFL